Examination of the bioelectrical activity of the masticatory muscles during Angle’s Class II division 2 therapy with an activator - Petrović Đorđe; Vujkov Sanja; Petronijević Branislava; Šarčev Ivan; Stojanac Igor (Vojnosanitetski Pregled)
Background/Aim. The muscles of the orofacial region have great influence on the development of dentition and occlusion formation. It is known that improper function of these muscles is one of the major etiological factors in malocclusion. A correlation between function disorders of orofacial muscle and occlusion disorders has been confirmed, as well as a correlation between the bioelectric activity of the masticatory muscles, recorded by electromyography, and bite force upon maximal voluntary contraction of these muscles. The aim of the study was to analyze the bioelectriacal activity of temporal and masseter muscles. Methods. The sample consisted of 100 subjects of both sexes, divided into the control group (n = 30) with neutral and complete dental arches, and the study group (n = 70) of patients with distal occlusion. Electromyographic measurement of bioelectric potentials in all the subjects was conducted for the examined muscles in the physiologic rest position, central mandible occlusion, and during maximal voluntary contraction of muscles and saliva swallowing, in Angle Class I and II/2 occlusal relation-ships, prior to treatment, after one year of the orthodontic treatment and after the treatment with an activator. Results. Comparing the values of thebioelectrical activity in the control and the study group before the treatment, a decreased muscle activity was established in all the three positions in the study group. After the first year of orthodontic treatment the results showed an elevation in the bioelectrical activity in both muscles. After treatment with an activator, the bioelectrical activity in both muscles in the study group was higher than before the treatment, as it is confirmed by a positive highly significant coefficient of correlation. Conclusion. In all the three measured positions of the mandible with Angle Class II/2 malocclusion, bioelectrical activity was lowest at baseline and increased during the first year of treatment, and at the end of the treatment it partially reduced close to the approximate values in normal occlusion. Research on electromyographic activity of masticatory muscles is useful in everyday clinical practice, especially in present distinctive skeletal discrepancy before, during and after orthodontic treatment, if on the bases of the results we can evaluate the treatment, but also determine the start and duration of the retention period and retention device type.